THE ROLE OF FAMILY SPIRITUALITY IN THE UPBRINGING OF THE YOUNGER GENERATION (Euro-Asia Conferences, 2021)
The article raises the issue of educating a comprehensivelydeveloped generation, which is one of the main social tasks of society,closely related to the activities of the family. And also the article talksabout the importance of creating a physically strong, spiritually strong andintelligent healthy generation, which is the main task of the family. In thisregard, the author emphasizes that the country pays great attention tostrengthening the family and its upbringing, the spiritual well-being of thefamily, its place and importance for the stability of society.